Chicken and Poultry Consumption and Human Health: A Scoping Review of Available Research Literature. (7th June 2021) - Connolly, Gavin; Clark, Caroline; Byers, Adam; Campbell, Robyn; Reed, Jason; Campbell, Wayne
Abstract: Objectives: The purpose of this scoping review was to systematically search and chronicle the available scientific literature pertinent to chicken/poultry intake and human health. Methods: The protocol was uploaded to Open Science Framework (https://osf.io/2k7bj/ ) and was conducted in accordance with recommended guidelines from PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) extension for scoping reviews (PRIMSA-Scr). Studies and scientific literature of all types (observational, experimental, narrative/literature reviews, systematic reviews and meta-analyses) assessing chicken/poultry intake and human health were included. Results: A total of 13, 141 articles were identified and 540 met the inclusion criteria. Among these 540 articles, 215 articles focused on cancer morbidity and mortality; 23 on cancer risk factors; 38 on cardiovascular disease (CVD) morbidity and mortality; 42 on CVD risk factors; 32 on diabetes morbidity and mortality; 33 on diabetes risk factors; 43 articles on body weight and body composition, and; 179 categorized as "Other", which included nutrient status, psychological well-being/mental health, cognitive outcomes, microbiome outcomes, chronic kidney disease, non-alcoholic fatty liver disease, skin disorders, and fertility, among others. Among the included articles, 413 were observational, 93 were reviews and meta-analyses, and 78 were experimental. Conclusions: This inaugural scoping review that systematically identified existing scientific literature pertinent to poultry intake and human health provides a foundation for future systematic reviews and meta-analyses. It also underscores the need for new experimental research to complement the current preponderance of evidence from observational studies. Funding Sources: National Chicken Council